Application of the Southwell Method to Determine the Critical Load of Compression Rods Made of Nonlinear Materials - Marcinowski, Jakub; Sadowski, Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Experimental determination of the critical force of a compression bar made of linear material does not pose major problems. The widely used Southwell method is also applicable to bars with cross-sections varying in length. The purpose of the research undertaken was to demonstrate that this method can also be successfully applied to bars made of elastic materials exhibiting nonlinear [sigma]([epsilon]) characteristics.
Keywords: bar buckling; critical force; Southwell method; nonlinear material; analytical methods; numerical methods